The occurence of canopy gaps in some semi-natural Irish woodlands and the natural regeneration of tree species therein - Higgins, Gemma Thérèse (Trinity College (Dublin, Ireland). Department of Botany, 2001)
The reported failure of regeneration in British oakwoods and some observations of a dearth of saplings and young trees in Irish woods has prompted concerns about the ability of Irish semi-natural woodland to self-perpetuate. The native tree species are limited in number and generally light demanding, and their regeneration may be expected to occur in canopy gaps. However, little is known about the distribution of gaps in Irish woodland, and few quantitative data regarding regeneration in canopy gaps have been available. Observations in Irish woodlands suggest that the production of seed and establishment of seedlings is sufficient for many species, but that saplings and young trees are absent. In some cases this has been attributed to the impact of heavy browsing by deer and domestic stock. The canopy disturbance regime was investigated using belt transects to sample 12 Irish woods. Disturbance events were identified, classified and their impact on the woodland canopy assessed. 45 canopy gaps from 13 woods were investigated in detail. Their formation, size, and other characteristics were described. Gaps were subjectively delineated into zones that differed structurally. The vegetation and specifically the regeneration of tree species were assessed for each gap. Variation in soil properties and vegetation with gap zone was investigated.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin